In-silico and in-vitro functional validation of imidazole derivatives as potential sirtuin inhibitor - Dindi, Uma Maheswara Rao; Sadiq, Suhadha Parveen; Al-Ghamdi, Sameer; Alrudian, Naif Abdurhman; Dayel, Salman Bin; Abuderman, Abdulwahab Ali; Shahid, Mohammad; Ramesh, Thiyagarajan; Vilwanathan, Ravikumar (Frontiers in Medicine, 2023)
Introduction Epigenetic enzymes can interact with a wide range of genes that actively participate in the progression or repression of a diseased condition, as they are involved in maintaining cellular homeostasis. Sirtuins are a family of Class III epigenetic modifying enzymes that regulate cellular processes by removing acetyl groups from proteins. They rely on NAD+ as a coenzyme in contrast to classical histone deacetylases (HDACs) (Class I, II, and IV) that depend on Zn+ for their activation, linking their function to cellular energy levels. There are seven mammalian sirtuin isoforms (Sirt1-7), each located in different subcellular compartments. Sirtuins have emerged as a promising target, given that inhibitors of natural and synthetic sources are highly warranted. Imidazole derivatives are often investigated as sirtuin regulators due to their ability to interact with the binding site and modulate their activity. Imidazole bestows many possible substitutions on its ring and neighboring atoms to design and synthesize derivatives with specific target selectivity and improved pharmacokinetic properties, optimizing drug development. Materials and methods Ligand preparation, protein preparation, molecular docking, molecular dynamics, density function theory (DFT) analysis, and absorption, distribution, metabolism, and excretion (ADME) analysis were performed to understand the interacting potential and effective stability of the ligand with the protein. RT-PCR and Western blot analyses were performed to understand the impact of ligands on the gene and protein expression of Class III HDAC enzymes. Results and discussion We evaluated the sirtuin inhibition activity of our in-house compound comprised of imidazole derivatives by docking the molecules with the protein data bank. ADME properties of all the compounds used in the study were evaluated, and it was found that all fall within the favorable range of being a potential drug. The molecule with the highest docking score was analyzed using DFT, and the specific compound was used to treat the non-small cell lung cancer (NSCLC) cell lines A549 and NCI-H460. The gene and protein expression data support the in-silico finding that the compound Ethyl 2-[5-(4-chlorophenyl)-2-methyl-1-H-Imidazole-4-yl) acetate has an inhibitory effect on nuclear sirtuins. In conclusion, targeting sirtuins is an emerging strategy to combat carcinogenesis. In this study, we establish that Ethyl 2-[5-(4-chlorophenyl)-2-methyl-1-H-Imidazole-4-yl) acetate possesses a strong inhibitory effect on nuclear sirtuins in NSCLC cell lines.